2003
DOI: 10.1023/a:1023524727484
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We recently reported a theoretical characterization of representative ensembles of statistical-coil conformations for tetrapeptides with unblocked termini in aqueous solution, at pH 7. The results showed good agreement between the computed Boltzmann-averaged and experimentally-determined values for both the vicinal coupling constants (3)J(NHalpha) and the alpha-proton chemical shifts. Here, we carry out a cluster analysis of the ensembles of conformations generated in that study, and use them to compute the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…These data are in opposite sign to the experimental data that of 5 ([α] D 23 +18.0) and 6 ([α] D 23 +22.6), indicating 5 and 6 to be the enantiomers of the calculated isomers. These assignments were also supported by the relative shift errors of the experimental 13 C NMR data of 6 and 5 that were in accordance with the error distribution calculated at B3LYP/6-311+G(2 d , p ) level (Table 3) [16]. Thus, the absolute configurations of 5 were in agreement with 7 R ,8 S ,11 S , whereas those of 6 were assigned to 7 S ,8 S ,11 S .…”
Section: Resultssupporting
confidence: 81%
“…These data are in opposite sign to the experimental data that of 5 ([α] D 23 +18.0) and 6 ([α] D 23 +22.6), indicating 5 and 6 to be the enantiomers of the calculated isomers. These assignments were also supported by the relative shift errors of the experimental 13 C NMR data of 6 and 5 that were in accordance with the error distribution calculated at B3LYP/6-311+G(2 d , p ) level (Table 3) [16]. Thus, the absolute configurations of 5 were in agreement with 7 R ,8 S ,11 S , whereas those of 6 were assigned to 7 S ,8 S ,11 S .…”
Section: Resultssupporting
confidence: 81%
“…Only 13 Cα- and 13 Cβ-Ala peaks were observed by rINEPT; no 13 CO-Ala signal was detected due to the absence of directly bonded protons. The tallest intensities in 13 Cα- and 13 Cβ-Ala line shapes were observed at 50.5 and 17.3 ppm, respectively, which are consistent with the random coil assignment. , This mobile environment is presumably described by fast large-amplitude fluctuations, which have motional time scales that are compatible with observation by rINEPT, τ c < 10 –9 s (recalculated for ∼9.4 T). , Such fluctuations may be related to structural interconversions described for statistical coils. In contrast, the 13 C-Ala CP spectrum reflects the relatively rigid regions in elastin (Figure , red). The absolute CP intensities are significantly lower than the rINEPT and DP spectra due to reduced dipolar couplings in the hydrated sample.…”
Section: Results and Discussionsupporting
confidence: 68%
“…Since peptides and proteins undergo significant structural fluctuations at biologically relevant temperatures, it is expected that their instantaneous chemical shifts will also fluctuate significantly. The effects of conformational averaging, as well as those due to the presence of the periodicity of the solid-phase environment, have been investigated in the literature for a variety of systems. In particular, the introduction of a method capable of describing the bulk behavior of condensed phases through the use of periodic boundary conditions has recently enabled the analysis of the effects of conformational averaging on proton chemical shifts of ice and liquid water by extracting conformations from trajectories generated by the Car−Parrinello molecular dynamics simulations. This type of study has been extended by, among others, Sebastiani and Parrinello, who reported fluctuations up to 10 ppm for proton chemical shifts in water, and more recently by Dumez and Pickard, who showed that motional averaging is an essential component of chemical shift calculations in organic solids.…”
Section: Introductionmentioning
confidence: 99%